ASUHAN KEPERAWATAN PADA BALITA RESIKO KEJANG DEMAM BERULANG DENGAN PENINGKATAN SUHU TUBUH DI RSU Dr. WAHIDIN SUDIRO HUSODO MOJOKERTO - NAFISAH, DURROTUN (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2017)
Febrile convulsion in children are fairly common disease in under five children. The increase of body temperature is very concerned to patient with febrile convulsion, because the increase of high body temperature will triggers recurrence of convulsion. The purpose of this research design was to perform nursing care on febrile convulsion with nursing problem of the risk of febrile convulsion recurrence.The research design was a case study with one respondent who diagnosed with febrile convulsion and had the risk of febrile convulsion recurrence. Data collection methods were interviews, observation, and documentation using format nursing care for children. Assessment used four main sources, namely the client, the nurse, the client's family, and the medical record. Then enforced nursing diagnosis, intervention, implementation, and evaluation.From the assessment obtained data mother said her child was having fever, lips slightly red, fussy, had convulsion ± 3 times during at the puskesmas. Body temperature was 37,7oC, pulse rate was 113x/ minute, respiration rate was24x/ minute. From the result of assessment the nursing diagnose was recurrence of febrile convulsions and ineffectiveness of thermoregulation.The result of data from complaint and condition of client there was nursing problem of the risk offebrile convulsion recurrence and ineffectiveness of thermoregulation. Intervention conducted was assesed history of seizures , giving health education about febrile Convulsion, warm compress, monitoring vital signs regularly, and take action of interdependent. The result of evaluation nursing care in 3 days nursing problem of febrile convulsion recurrence and ineffectiveness thermoregulation resolved.Key words: Nursing care, Recurrence febrile convulsion, Hypertermia.